Phonetic and Syntactic Stylistic Means in Media Space: Manipulation or Emotional Commonplace? - Stashko, Halyna (Communication Today, 2018)
The essay presents research of video and audio texts featuring public personalities for usage of phonetic and syntactic stylistic means in their speeches, aiming at identifying whether a set of phonetic and syntactic devices may enable deliberate manipulation or remain commonplace showing mere melodic patterns in speech. The analysis embraces schemes of stylistic overlapping and isolation, examines their effect within a speech and outlines cultural, gender and social backgrounds of the speaker and the audience, their correlation and ‘dialogue’ on the touch points. Taking into consideration the idea that any influence of famous personalities must have its achievement point and relevant feedback, it is possible to speak of media as of a bridge to human minds, a key to their hearts and a trigger to their behavioural patterns.